Development of a mixed feed strategy for a recombinant Pichia pastoris strain producing with a de-repression promoter. Issue 1 (December 2015) - Capone, Simona; Horvat, Jernej; Herwig, Christoph; Spadiut, Oliver
Abstract Background Recombinant protein production in the yeastPichia pastoris is usually based on the alcohol oxidase promoters pAOX1 and pAOX2, which are regulated by methanol and strongly repressed by other C-sources, like glycerol and glucose. However, the use of methanol brings several disadvantages, which is why current trends in bioprocess development withP. pastoris are focussing on minimizing the required amount of methanol or even avoid its employment. In this respect novel promoter systems which do not rely on methanol have been investigated and promoter variants were designed to fine-tune gene expression. Amongst these novel promoter systems, mutated AOX promoters, which are regulated by available carbon source concentration (so-called de-repressed promoters), are currently raising attention. However, the main disadvantage of such a production system is that expression and growth usually cannot happen concomitantly resulting in low space–time-yields. Results Here we show the development of a mixed-feed strategy for an industrial recombinantP. pastoris de-repression strain aiming at increased productivity and maximum space–time-yield. By doing dynamic experiments we determined a ratio between the specific substrate uptake rates of glycerol and sorbitol allowing a more than 2-fold increased productivity compared to the conventional single substrate de-repression strategy. Conclusion Based on our results we recommend adjusting qs glycerol  = 0.04 g g−1  h−1 and qs sorbitol  = 0.055 g g−1  h−1 to obtain highest productivity with aP. pastoris de-repression strain. Our methodological approach of designing mixed-feed strategies based on physiological strain characterization using dynamic experiments proved to be beneficial.